First Australian experience of treating localised prostate cancer patients with CyberKnife stereotactic radiotherapy: early PSA response, acute toxicity and quality of life. Issue 3 (8th March 2017) - Dixit, Ashutosh; Tang, Colin; Bydder, Sean; Kedda, Mary‐Anne; Vosikova, Eva; Bharat, Chrianna; Gill, Suki
Abstract: Introduction: This study is to evaluate biochemical response, acute toxicity and health‐related quality‐of‐life (QOL) outcomes among prostate cancer patients following stereotactic body radiation therapy (SBRT) in the first Australian CyberKnife facility. Methods: Forty‐five consecutive patients with clinically localised prostate cancer were treated with SBRT using CyberKnife technology and enrolled in this study. Protocol treatment consisted of 36.25 Gy in five fractions. PSA and acute toxicity was assessed at each follow‐up visit and QOL was assessed using the European Organisation for Research and Treatment of Cancer (EORTC) Global Health Status (GHS) C30 and PR25 questionnaires and the Karnofsky Performance Status (KPS). Distance of travel for treatment was recorded. Results: The median prostate‐specific antigen (PSA) level declined from the initial value of 6.9 ng/mL to 1.5 ng/mL at 6 months and 0.6 ng/mL at 18 months post‐treatment. Results were similar in patients who did not receive hormone therapy. Acute grade 1 gastrointestinal (GI) and genitourinary (GU) toxicities were found in 11.1% and 24.4% of patients respectively. Acute grade 2 GI and GU toxicities were found in 2.2% and 11.1% of patients respectively. There were no grade 3 and grade 4 toxicities. Mean urinary symptom score was 14.8 at baseline, 17.2 at 6 weeks and 18.3 at 6 months ( P > 0.05). Mean bowel symptom score was 2.7 at baseline, 4.2 at 6 weeks and 6.3 at 6 months ( P > 0.05). The mean GHS score improved from 81.3 at baseline to 82.4 at 6 weeks, and was 75.6 at 6 months ( P > 0.05, not significant). Compared to baseline KPS, there was a significant mean decrease from baseline of 96.7 to 93.3 at the 6‐week follow‐up ( P = 0.0043), which then recovered to 94.3 at the 6‐month follow‐up ( P = 0.1387). Conclusions: Early results show promising PSA response. Acute toxicity seemed comparable to results from conventionally fractionated radiotherapy and to international prostate SBRT studies. EORTC PR25 and C30 scores did not reveal any significant change from baseline, and although there was a decrease in KPS, the absolute decrease was small. Abstract : This study shows the early results of curative intent stereotactic body radiation therapy using CyberKnife technology for clinically localised prostate cancer for the first time in Australia.